Changes in cognition over a 16.1 km cycling time trial using Think Aloud protocol: Preliminary evidence. Issue 3 (4th May 2019) - Whitehead, Amy E.; Jones, Hollie S.; Williams, Emily L.; Dowling, Christopher; Morley, David; Taylor, Jamie A.; Polman, Remco C.
Abstract : Objectives : This study investigated cognitions of cyclists during a competitive time trial (TT) event using Think Aloud (TA) protocol analysis. Design : Single group, observational design. Method: Fifteen male and three female cyclists from the North West of England verbalised their thoughts throughout an outdoor competitive 16.1 km cycling TT (Level 2 TA). Verbalisations were recorded using iVue Horizon 1080P camera glasses. Data were transcribed verbatim, analysed using deductive content analysis and grouped into themes: (i) Pain And Discomfort (Fatigue, Pain), (ii) External Feedback (Time, Speed, Heart Rate), (iii) Environment (Surroundings, Traffic and Other Cyclists), and (iv) Pace and Distance (Pace, Distance). The number of verbalisations within each theme was analysed by distance quartile using Friedman tests to examine changes in cognitions over time. Results : Associative themes, including Fatigue and Pain, were verbalised more frequently in the earlier stages of the TT and less in the final quartile, whereas verbalisations about Distance significantly increased in the last quartile. Conclusions : This study demonstrates how a novel data collection method can capture in-event cognitions of endurance athletes. It provides an important extension to previous literature, showing how individuals may process and attend to information over time during an exercise bout. Future research should establish the relationship between performance and cognitive processes.